Dispatches from the Fort Apache scout : White Mountain and Cibecue Apache history through 1881 - Davisson, Lori; Perry, Edgar (The University of Arizona Press, 2016)
"The book continues efforts to bridge Ndee (Apache) and non-Indian ideas about what happened in the past and why history matters today. It stakes out a common ground for understanding the earliest relations between very different groups: Apache, Spanish, Mexican, and American"--Provided by publisher.